2005
DOI: 10.1086/427819
|View full text |Cite
|
Sign up to set email alerts
|

TheB‐Band Luminosity Function of Red and Blue Galaxies up toz= 3.5

Abstract: We have explored the redshift evolution of the luminosity function of red and blue galaxies up to z ¼ 3:5. This was possible by joining a deep I-band composite galaxy sample, which includes the spectroscopic K20 sample and the Hubble Deep Field samples, with the deep H AB ¼ 26 and K AB ¼ 25 samples derived from the deep NIR images of the Hubble Deep Field-North and Hubble Deep Field-South, respectively. About 30% of the sample has spectroscopic redshifts and the remaining fraction well-calibrated photometric r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
184
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 98 publications
(232 citation statements)
references
References 53 publications
45
184
3
Order By: Relevance
“…-Our results add new evidence in favour of constant slope of the C-M relation in clusters, at least up to z = 1 implying a constant mass-metallicity relation, according to the standard interpretations. -Our analysis shows that the average C-M relation for galaxies belonging to the red population is consistent with a linear extrapolation of the relation found by Bell et al (2004) up to z = 1.5, complementing the results of Giallongo et al (2005), who have shown that the blueing of the average colour of the red galaxies extends to z ≈ 2−3.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…-Our results add new evidence in favour of constant slope of the C-M relation in clusters, at least up to z = 1 implying a constant mass-metallicity relation, according to the standard interpretations. -Our analysis shows that the average C-M relation for galaxies belonging to the red population is consistent with a linear extrapolation of the relation found by Bell et al (2004) up to z = 1.5, complementing the results of Giallongo et al (2005), who have shown that the blueing of the average colour of the red galaxies extends to z ≈ 2−3.…”
Section: Discussionsupporting
confidence: 89%
“…This assumption is justified by the analysis of Blakeslee et al (2003) who find a constant slope for different galaxy clusters up to z = 1.2 (see the next paragraph). At higher redshifts Giallongo et al (2005) find a decrease of the red sequence slope ∂(U −V) rest /∂M B rest from −0.098 to −0.062, in the two wide redshift bins 0.4-1 and 1.3-3.5 respectively. In the present analysis, which is limited to z < 1.7, we neglect this change of slope and we estimate the red sequence colours in three relatively narrow redshift bins.…”
Section: Cosmological Evolution Of the Red Sequencementioning
confidence: 83%
See 2 more Smart Citations
“…A bimodality in galaxy colours up to z ∼ 2 was also found by Cassata et al (2008) in the GMASS field and Giallongo et al (2005) in the HDF. The latter also showed that the blue and red galaxy populations most probably had different evolutionary histories.…”
Section: Red Sequencesupporting
confidence: 65%